AIR TEMPERATURE EFFECT ON END OF FLOWERING OF CIRSIUM ARVENSE (L.) SCOP. IN A MOUNTAINOUS REGION OF GREECE - Aristidis Matsoukis; Athanasios Kamoutsis; Aikaterini Chronopoulou-Sereli (Journal of Animal and Plant Sciences, 2018)
The quantitative determination of plant phenophases in mountainous warmer and colder regions is very useful information regarding evaluation of possible climatic variability and plant ecological success. No such information is available about one of the top weeds within agriculture, Cirsium arvense (L.) Scop. Thus, the impact of the average air temperature (T) of September and October on the onset (julian days) of the phenophase ‘End of flowering’ of C. arvense was studied at two areas of a mountainous region of Nafpaktia, Greece, Evinos River (823 m alt.) and Sarantena (1431 m alt.) for eight consecutive years (2007-2014). Sarantena was characterized as lower values of average T as compared to Evinos River. ‘End of flowering’ appeared later in Evinos River compared to Sarantena. The earliest and latest onset of ‘End of flowering’ took place in 2011 and 2012, respectively, for both examined areas. The ‘End of flowering’ onset correlated positively with the average T of October. The increase of 1 °C caused a delay of the onset of the examined phenophase by 8.49 and 5.70 julian days in Evinos River and Sarantena, respectively. The results of this study may contribute to planning of an effective control program of C. arvense.
Keywords: air temperature; altitude; Cirsium arvense (L.) Scop.; End of flowering; mountainous Nafpaktia; phenology; river